Sonication of porphyrin-nanotube composites: a cautionary tale - GIORDANI, SILVIA; BLAU, WERNER (My University, 2007)
We report the spectroscopic changes of tetraphenylporphyrin carbon nanotube composites in a variety of chlorinated solvents such as chloroform, dichloroethane and dichlorobenzene as a result of sonication. Detailed data analysis suggests that protonation of the porphyrin core nitrogen atoms occurs as a result of sonodegradation of the solvent molecules. Extreme care must be taken when working with carbon nanotube composite solutions in chlorinated solvents, as sonication is always employed to disperse the nanotubes. This finding is of enormous relevance to the materials chemistry community since these solvents are widely used in preparation of carbon nanotube composite solutions. When working with molecules that are capable of acting as a base some amount of protonation is inevitable and this may dramatically change the physicochemical properties of the composite materials.
PUBLISHED
Keywords: Chemistry